IDENTIFIKASI BAKTERI POTENSIAL PROBIOTIK PADA SALURAN PENCERNAAN IKAN PATIN SIAM (Pangasius hypophthalmus) - Siska Sitohang; Dwi Suryanto; Yoes Soemaryono (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2018)
The aim of this study was to isolate potential probiotic bacteria from gastrointestinal tract of Patin Siam (Pangasius hypophthalmus) and to examine its potential in inhibiting Aeromonas hydrophila growth. De Man Ragosa Sharpe Agar was used to isolate potential probiotic bacteri. Characterization including Gram stain, Probiotic test, catalase test, and motility test was conducted. All isolates showed characterization of probiotic bacteria. Four isolates was identified as Bacillus coagulans, Bacillus badius, Streptococcus bovis type I and Micrococcus roseus. Antimicrobial test against A. hydrophila showed that all potential probiotic isolatest inhibited A.hydrophila growth with inhibition zone of 7-9 mm.Keyword: Probiotic Bacteria, Patin Fish, Bacillus coagulans, Streptococcus bovis type I, Bacillus badius and Micrococcus roseus.